Aplikasi Pewarnaan Graf terhadap Penyimpanan Bahan Kimia - Mahmudah, Muhlisatul (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2022)
Graf G = (V, E), where V is the set of points and E is the set of sides. An interesting application of graphs, one of which is graph coloring. There are three kinds of coloring that are point coloring, edge coloring, and region coloring. This paper will be studied dye staining. Point coloring is coloring the dots of a graph so that no two neighboring dots have the same color. The minimum number of colors that can be used to color a graph is expressed by chromatic numbers. Currently a lot of applications for graph coloring, one of which is the storage of chemicals. The storage of chemicals required a good arrangement, this is due to the influence of chemicals on each other if stored simultaneously. The main focus of this paper is to determine the chromatic number in the graph and the application scheme of dye graph coloring.